2011
DOI: 10.1152/japplphysiol.00942.2010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anti-inflammatory medication on the running-induced rise in patella tendon collagen synthesis in humans

Abstract: NSAIDs are widely used in the treatment of inflammatory diseases as well as of tendon diseases associated with pain in sports and labor. However, the effect of NSAID intake, and thus blockade of PGE(2) production, on the tendon tissue adaptation is unknown. The purpose of the present study was to elucidate the possible effects of NSAID intake on healthy tendon collagen turnover in relation to a strenuous bout of endurance exercise. Fifteen healthy young men were randomly assigned into two experimental groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 38 publications
2
55
1
Order By: Relevance
“…Thus it has been demonstrated that NSAID was able to diminish the PGE 2 response to mechanical loading of human fibroblasts isolated either from patellar tendon or from hand tendon that were stretched in vitro (1,26). In humans, we investigated the effect of NSAID on the local peritendinous concentration of PGE 2 along the surface of human patella tendon and demonstrated that, when anti-inflammatory medication was provided for 3 days before the experiment, local PGE 2 levels were lower at 72 h after exercise compared with the nonblocked situation (8). Along with this blockade of inflammatory mediators, the exercise-induced increase in peritendinous collagen synthesis was reduced (8).…”
Section: Role Of Inflammatory Mediators In Adaptation Of Healthy Tendmentioning
confidence: 99%
“…Thus it has been demonstrated that NSAID was able to diminish the PGE 2 response to mechanical loading of human fibroblasts isolated either from patellar tendon or from hand tendon that were stretched in vitro (1,26). In humans, we investigated the effect of NSAID on the local peritendinous concentration of PGE 2 along the surface of human patella tendon and demonstrated that, when anti-inflammatory medication was provided for 3 days before the experiment, local PGE 2 levels were lower at 72 h after exercise compared with the nonblocked situation (8). Along with this blockade of inflammatory mediators, the exercise-induced increase in peritendinous collagen synthesis was reduced (8).…”
Section: Role Of Inflammatory Mediators In Adaptation Of Healthy Tendmentioning
confidence: 99%
“…However, other studies have shown that NSAIDs inhibit proliferation of tendon cells but increases collagen synthesis (49). Furthermore, mechanical loading can up-regulate prostaglandin E synthase which in turn is regulated by COX activity (12,45). This suggests that the impairment of tendon healing by COX-2 inhibition might be dependent on the degree of loading, which we could not show.…”
Section: Comparison With Other Studiescontrasting
confidence: 70%
“…These mediators are important during inflammation but they can also have other functions such as during mechanotransduction (12,49,53,54,56). Prostaglandin E2 and its enzyme prostaglandin E synthase (PTGES), as well as COX-2, are increased by mechanical loading and seem to play a role during mechanical stimulation in tendons and tenocytes (12,40,45,53,54). The enzyme, PTGES, is upregulated by both full loading and microdamage by needling in healing tendons, which suggests that prostaglandin E2 is important during these stimulations (17, 28 (Paper IV)).…”
Section: Mechanotransduction and Microdamage Stimulates Tendon Healinmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of the same human muscle biopsies collected 8 days after a single bout of eccentric contractions, where an inhibitory effect of NSAID exposure on satellite cell proliferation was observed (47), no influence of NSAIDs was detected on collagen gene expression levels or the fractional synthetic rate of collagen synthesis (48). With regard to other tissues, NSAID ingestion (beginning 3 days before exercise and continuing until the end of the study) has been reported to suppress the collagen synthesis response to exercise around human tendon tissue (16), in contrast to a study of rat Achilles tendon cells exposed to ibuprofen, which demonstrated an upregulation of genes for collagenases compared with untreated cells, while no effect on collagen types I or III was observed (80). In a rat osteoarthritis model, long-term NSAID ingestion has been reported to upregulate the protein levels of collagen types I and III in articular cartilage (54).…”
Section: Effects Of Nsaids On Factors Influencing Satellite Cellsmentioning
confidence: 99%